What Drives Blue-Collar Workers Transition in The Labor Market Dynamics? Lesson Learned from Indonesia - Christiayu Natalia; Devanto Shasta Pratomo; Wildan Syafitri (Universitas Negeri Malang, 2024)
The recovery from the global pandemic, as well as improvements in automation technologies, have presented substantial challenges for blue-collar workers who specialized in manual work. Labor transition is considered a strategy to adapt and strengthen their resilience. This study utilizes Indonesian National Labor Force Survey / SAKERNAS data from August 2023 to examine the key factors influencing blue-collar worker transitions in Indonesia, including three primary outcomes: (1) remaining unemployed and inactive, (2) transitioning back to the blue-collar worker, and (3) transitioning to the white-collar worker. The study employs multilevel multinomial logistic regression to examine the influence of individual characteristics (e.g., gender, marital status, age, education, migration, training, employment card possession, and area of residence) and regional characteristics (e.g., internet penetration, minimum wage levels, and municipal economic growth) on labor transitions. Results reveal that both individual and regional characteristics significantly impact these transitions. To address these challenges, enhancing human capital through targeted technical training is essential to improve the resilience and adaptability of blue-collar workers in Indonesia's dynamic labor market. This research emphasizes the importance of policy in equipping the blue-collar worker to navigate the evolving demands of the labor market.